Identification and characterization of QTL for grain protein content derived from the D genome of allohexaploid wheat - Luo, Xinghua; Shao, Tianjiao; Zhai, Shanshan; Meng, Xinhao; Wen, Shidian; Xie, Chaojie; You, Mingshan; Liang, Rongqi; Ni, Zhongfu; Sun, Qixin; Zhang, Runqi; Li, Baoyun (Frontiers in Plant Science, 2025)
IntroductionIdentifying and utilizing major quantitative trait loci (QTLs) related to wheat grain protein content (GPC) is critical for the wheat quality improvement. However, the identification of genes regulating GPC remains relatively limited.MethodsIn this study, a genetic population containing 198 recombinant inbred lines (RILs), derived from a cross between common allohexaploid wheat cultivar TAA10 and synthetic allohexaploid wheat cultivar XX329 was used to identify QTLs associated with GPC.ResultsThree major QTLs for GPC were detected on chromosomes 2D, 4D, and 7D (Qgpc.cau-2D, Qgpc.cau-4D, and Qgpc.cau-7D) respectively. Among them, QGpc.cau-2D located between markers Xbarc124 and 2S178, exhibited the largest additive effect and explained 4.70-17.97% of the phenotypic variation. Using progenies from the key residual heterozygous line124, QGpc.cau-2D was fine mapped to an approximately 4.2 Mb physical interval between the markers Xcau-2D541 and Xcau-2D781. According to the analysis of genes within the interval, TraesCS2D03G0079200, TraesCS2D03G0080700, TraesCS2D03G0081400, and TraesCS2D03G0088900 were predicted as putative candidate genes.DiscussionThese results provide a foundation for the cloning of candidate genes related to GPC and the genetic improvement of wheat quality.